The Modelery: a model-based software development repository - Couto, Rui (2015)
Purpose – This paper aims to present the Modelery, a platform for collaborative repository to support model-based software development. The Modelery is a Web platform, composed both by a Web page and Web services for interoperability. Design/methodology/approach – By performing a study in the existing platforms, it was possible to achieve a set of issues to tackle. The issues enabled the possibility to define a set of requirements that allowed the authors to design a new platform, and to perform a model-driven software development process, which started from the requirements until reaching the final software solution. Findings – With this work, it was possible to perform a survey on the currently available artifacts repositories, categorize them and identify their shortcomings. This was essential to define the set of requirements for a new platform to overcome the identified issues. This process leads to a platform able to improve the currently available solutions, and validated in the scientific community. In this paper, the authors also explore the applications of the repository. First, they use the Modelery to replace an older model’s repository. Second, they have enabled the communication between other tools and the Modelery via Web services. Originality/value – This work presents a new Web repository for software artifacts aimed at supporting researchers and software developers. The presented platform is an improvement over other platforms on the integration of artifacts repository, social functionalities and scientific publications integration. The authors conclude this paper by comparing the achieved platform in terms of functionalities, against the other analyzed platforms.